ANALYSIS OF COST OF PRODUCTION USING METHOD FULL COSTING AND VARIABLES COSTING IN THE SPACE COFFEE HOUSE YEAR 2022 - Tulus Pujo Nugroho (International Journal Multidisciplinary Science, 2024)
This scientific writing aims to determine the calculation of the cost of production in Ruwang Coffee House using method full costing and variables costing. Determining the cost of production is very important in determining competitive prices, so that the business can compete in the market and can increase business income. The data collection methods used in this research were interviews and observation. Interviews were conducted directly with business owners. This research uses quantitative data and the data used is primary data, where the data was obtained directly by Ruwang Coffee House. The data obtained includes the number of sales, raw material costs, labor costs and factory overhead costs. From the research that has been carried out, the author concludes that the calculation of the cost of production uses the method full costing has a greater value when compared to using the variable method costing, this is due to the method full costing charge all costs overhead factory, method full costing better to use than using the variable method costing.